Corporalidade brasileira na fabricação da identidade nacional - Ana Lúcia Castro; Renata Pires Pinto (Ciências Sociais Unisinos)
This paper discusses how, through the creation of Embratur (Brazilian Tourism Company) in 1966, an idealized Brazilian female body was constructed and used to help manufacture a national identity, reinforcing the stereotype of the sexualized Brazilian woman. As it was often associated with sex tourism, this stereotype received much criticism and led to a negative image of Brazil abroad. However, in the 1990s the official tourism lobby softened the “sexy tone” of its discourse, and in 1999 Embratur received an award from the World Tourism Organization for its campaign to help fight the exploitation of children and youth by sexual tourism. In order to better understand how this change in the idealized Brazilian female body unfolded, it is important to deconstruct beauty standards – focusing on those that apply to Brazilian women as seen from abroad – and their relationship to modern consumer culture. Assuming that the cultural analysis of the female body emerges as an important issue in the field of Social Science, the focus on body image can be viewed as a key element in discussions about the construction of national identity.